T(og)ether: technological attachment and personal detachment: an ethnography of athletes with disabilities and support guides running the New York City Marathon 2019 - Serra, Gabriella (My University, 2020)
Due to the multivalent nature of support and assistance, I aim to better understand what it means to provide “support” and “assistance”, especially for individuals with physical disabilities participating in mainstream sporting events. In this research report, I argue that the prevalence and implementation of (bio)technology’s assistive wearables and their predetermined algorithms dis-able such people from wanting to participate in such events. Such devices are not able to accommodate the complex human experiences, environmental engagement or support systems that are enabling factors for people to participate in a community activity. Within the sporting domain, one’s sense of self and physical self-perception is of vital importance if one wants to succeed. In this study, I examine how participation in one mainstream sporting event, the 2019 New York City Marathon, is challenged and reimagined by bodies defying the social norm of the sportsperson. Through personal narratives of individuals with and without physical disabilities who participated in the marathon, I critique technological forms of assistance. Through active participant observation I have developed an alternative framework to rethink what it means to support and assist a particular human experience and embodied sense of being-in-the-world that cannot be reduced to predetermined quantifiable metrics. As supported by both the literature reviewed and my ethnography, an understanding and acknowledgement for the importance of embodied knowledge, physical self-perception, sensory engagement and the reciprocal nature of support and assistance from one physical body to another is fundamentally important to enable sports participation for all individuals. The intricacies of subjective experience and human connection should not be mediated by an impersonal attachment to an objectified device. In this research report, I demonstrate how human beings both physically and socially create a sense of support and togetherness, despite their (dis)ability to become technologically tethered
A research report submitted in partial fulfilment for the degree of Masters of Arts in Anthropology, University of the Witwatersrand, Department of Anthropology, School of Social Sciences, 2020